Pembentukan Karakter Mandiri Siswa melalui Program Full Day School di MI Ya Bakii Welahan Wetan Adipala - Faizaturrohmah, Siti; Maspupah, Ulpah (Jurnal Pendidikan Agama Islam, 2025)
The formation of independent character is an effort to form morals, a person's personality that can distinguish each individual with the ability they have to do all activities without relying on others. This study aims to describe and obtain a comprehensive picture of how the process of forming independent character of lower grade students through the full day school program. The method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The validity test used is source triangulation and technique triangulation. Data analysis techniques include data reduction, data presentation, and conclusions. The results of the study indicate that the implementation of the full day school program consistently contributes to the formation of students' independent character. Internalization of the formation of independent character of lower grade students intensively through the full day school program at MI Ya Bakii Welahan Wetan is actualized by instilling and implementing daily habits, and also supporting activities of full day school such as reciting the Koran, afternoon learning, and outing classes. In this way, children become more independent in their daily activities such as doing assignments, eating alone, tidying up learning tools, daring to express opinions, taking the initiative and being responsible.